The Role Of River-Lake Transportation Company In Handling Body Electricians: Case Study On MV. Rhodos PT. Indo Dharma Transportation - Awel Suryadi; Roni Tri Handoyo (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
Evacuation is a step taken to get first aid at that time. PT Indo Dharma of the River-Lake Transport Branch serving the ship must play a role in handling. On July 15, 2021, there was an incident above the MV. Rhodos, one of the crew members, Electricians, suffered a heart attack after a full day of repairs to a damaged crane. This research uses a qualitative description method by means of observation, interviews, and literature methods. Based on the study's results, it was found that the problem occurred, namely the distance between the port and the position of the MV ship. Rhodos and the distance between the port and clinic is quite far, the handover of the body from the agency to the insurance company takes a long time so it has an impact on the evacuation process which is quite long, and first aid by the medical party only when at the port and travel. PT. Indo Dharma of the River-Lake Transport Branch plays a very active role in facilitating supporting facilities and infrastructure efficiently and effectively by cooperating, coordinating, and communicating well with related parties and should each agency company have Standard Operating Procedures for handling deceased ship crews and socialized to agents on duty in the field so that they understand and understand what actions must be taken immediately when the same event occurs.